2012
DOI: 10.1186/1742-6405-9-15
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality among HIV infected patients taking antiretroviral treatment in Ethiopia: a retrospective cohort study

Abstract: BackgroundStudies indicate that there is high early mortality among patients starting antiretroviral treatment in sub-Saharan Africa. However, there is paucity of evidence on long term survival of patients on anti-retroviral treatment in the region. The objective of this study is to examine mortality and its predictors among a cohort of HIV infected patients on anti-retroviral treatment retrospectively followed for five years.MethodsA retrospective cohort study was conducted among HIV infected patients on ART … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

41
60
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 19 publications
41
60
4
1
Order By: Relevance
“…Similarly, other studies in Ethiopia [27,31] showed that there is higher mortality in patients with lower baseline functional status similar to the present study. Two other studies in Africa showed that patients who experienced severe morbidity and hence poor performance at presentation to health facilities had higher risks of mortality [32,33] highlighting the need for early presentation and screening for HIV as well as TB of the general population in Africa.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Similarly, other studies in Ethiopia [27,31] showed that there is higher mortality in patients with lower baseline functional status similar to the present study. Two other studies in Africa showed that patients who experienced severe morbidity and hence poor performance at presentation to health facilities had higher risks of mortality [32,33] highlighting the need for early presentation and screening for HIV as well as TB of the general population in Africa.…”
Section: Discussionsupporting
confidence: 79%
“…This finding was comparable to results of two retrospective cohort studies in Eastern Ethiopia [26,27]. This clearly indicates that ART should be initiated as early as possible such as before CD4 counts drop down to 200cells/mm 3 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Poor adherence leads to clinical failure, resulting in poor CD4 count, giving rise to OIs, and thereby increasing the risk of mortality. Various studies conducted across the globe have reported that poor adherence to ART increases mortality [15,28,29]. The results from our study as well as from similar studies across the world have pointed towards a variety of factors which predict mortality among PLHIV.…”
Section: Discussionsupporting
confidence: 68%
“…Studies from the Sub-Saharan African region have observed a similar trend, with respect to the role of nutrition in PLHIV. Low BMI was associated with mortality in studies from Burkino Faso [9,14], northern Ethiopia [10] and Nigeria [11], where, as in studies from Tanzania [6] and Ethiopia [15], history of significant weight loss, and weight less than 45 kg were predictors of mortality. Poor nutritional status at the initiation of ART and its deterioration within the first 3 months of starting therapy was an important predictor of mortality in another study from Tanzania [16].…”
Section: Discussionmentioning
confidence: 97%